ANALISIS FAKTOR INTERNAL - EKSTERNAL DAN STATUS KEBERLANJUTAN PENGELOLAAN PERIKANAN TANGKAP DI TELUK JAKARTA - Radarwati, Siti; Baskoro, Mulyono S.; Monintja, Daniel R.; Purbayanto, Ari (Jurnal Teknologi Perikanan dan Kelautan, 2017)
The capture fishery at Jakarta Bay has a big role in increasing the economy and community life at the site, but its not only faced the decreasing fishery production and high poluted water teritory, its sometime confronted with the conservation function located in Kepulauan Seribu. The objectives of this reasearch were to determine internal and external factors that effects to capture fishery activity, to identify sustainable status of capture fishery management in Jakarta Bay and its development management strategy. The study used the methods of IFAS, EFAS and SFAS matrix analysis, IE matrix analysis and SWOT matrix analysis. The result revealed that there are 17 (seventeen) factors affecting the capture fishery activities in Teluk Jakarta at the point of view dimensions of ecological, biological, economic, social and technological. The scores output from matrix IFAS, EFAS and SFAS were all categorized as “kurang baik” with total score 2,529 for internal factors and 2.747 for external factor, and 2.152 for SFAS, respectively. The sustainable status for capture fishery management in Teluk Jakarta pointed out by IE matrix in the cell V categorized as developing status that need horizontally concentration strategy. The study identified that there are several important strategies to support the management sustainability of capture fishery : human resources empowerment, quality product improvement, increasing fishermen capability, increasing capture fishery activities supervision, extension for fishermen, integrated management to preserve the functions of water ecosystem, small scale fishery standardization and fishing days opreration management by implementing closed – open seasons